HUBUNGAN ANTARA HENDAYA KOGNITIF DAN GENOTIPE APOE 4 TERHADAP KEMANDIRIAN LANSIA - Eveline,* Yuda Turana,* Josephine Retno Widayanti* (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION THE PREVALENCE OF COGNITIVE IMPAIRMENT AND DISABILITY INCREASES WITH AGE SEVERE COGNITIVE IMPAIRMENT CAN LEAD TO AN INABILITY TO LIVE INDEPENDENTLY AND DECREASE ABILITY IN DOING MORE COMPLEX DAILY LIFE ACTIVITIES THE GENOTYPE OF APOE 4 AFFECTS COGNITIVE IMPAIRMENT AND IS ASSOCIATED WITH WALKING MOTOR SKILLS AND DISABILITY FUNCTIONS ELDERLY WITH APOE 4 WILL TEND TO EXPERIENCE INABILITY TO LIVE INDEPENDENTLY